Peran Board of Directors dalam Operational Risk Disclosure: Studi Empiris Perbankan Indonesia - Suhardjanto, Djoko; Rahmawati, Erna (Jurnal Trikonomika, 2012)
The purpose of this study is to examine the effect of board of directors to operational risk disclosure of Indonesian banks. Board of directors are identified as the board size, the composition of independent commissioners, the composition of woman commissioners, educational background of president directors, and the number of board meetings. This study also uses profitability and the composition of independent audit committee members as control variable. The level of operational risk disclosure is measured based on identified items of Lampiran Surat Edaran Bank Indonesia No.5/21/DPNP/2003. Under purposive sampling, secondary data of 46 annual reports year 2008-2009 of banks in Indonesian Stock Exchange are selected. The result of multiple regression shows that the size of board of directors affects the level of operational risk disclosure. Board of directors is the core of corporate governance, charged ensuring strategic guidance, monitoring management, and providing accountability. Other variables, the composition of independent commissioners, the composition of woman commissioners, educational background of president directors, and the number of board meetings are not good predictors for level of operational risk disclosures.